Bacillus cereus infection-associated pneumonia in an African grey parrot (Psittacus erithacus erithacus). (January 2016) - Sharma, Rinku; Rawool, Deepak; Patil, Rajendra; Mohan, V.; Kumar, Vijay; Parimoo, Haroon; Pati, Uma; Singh, Birbal; Bhat, Tej
Abstract Bacillus cereus infection-associated suppurative pneumonia was recorded in an adult African grey parrot (Psittacus erithacus erithacus ). Grossly, the diaphragmatic lung lobes showed presence of multiple, irregular, creamy colored areas over the surface. The adjacent parenchyma appeared congested and pneumonic. Histopathologically, multifocal areas of abscesses characterized by presence of necrotic cell shreds, fibrin, and collection of heterophils with presence of bacterial aggregates were observed in the lungs. Taylor's staining revealed presence of multiple aggregates of Gram-positive bacteria within fibrin shreds in the necrotic debris in the lungs. Other vital organs such as heart, liver, and brain revealed variably engorged and dilated blood vasculature, and the intestine showed hemorrhagic enteritis. Thus, based on above pathological findings and the partial sequence analysis report of 16S rRNA gene (919 bp) amplified from a DNA extracted from the lung tissue, B. cereus was predicted as a causative agent for the death of the psittacine bird. Thus, to the best of our knowledge, B. cereus -associated suppurative pneumonia in African grey parrot appears to be the first report from India.